TEMPERATURE CONTROLLER IN PORTABLE BOXES USING PID (PROPORTIONAL INTEGRAL DERIVATIVE) METHOD - Ach Dafid; Firmansyah Adiputra (International Journal of Science, Engineering, and Information Technology, 2022)
Many foods become unhealthy because they are contaminated with unsafe ingredients or with containers that are not suitable for use. One of them is by using plastic media, which often happens to workers and children when buying food carelessly. So it takes food supplies to still be able to control what is consumed. But many parents are not aware of the dangers of plastic being used to store food. Not only that, when the provisions use plastic media, the food cools very quickly in a matter of hours. So you need a food heater to keep it warm and fresh when consumed. Where a food box warmer can warm food in a short time of 15 minutes, using a PTC (Positive Temperature Coefficient) heating element to get a temperature value of 49 ÂºC using the PID (Propotional Integral Derevative) method which is used to get an error value and has a response stable system. PID can provide control with good accuracy during the heating process. So that the results of several experiments obtained a set point value of 49 ÂºC which has a stable temperature with an error rate of 0.69